Improvement in the early growth, immune system and tibia development of broilers in response to the in ovo injection of 25-hydroxyvitamin D3. Issue 1 (31st December 2023) - Xu, Hengyong; Hu, Zhi; Lu, Yuxiang; Jiang, Yuru; Li, Dan; Lei, Bingqian; Du, Ranran; Yang, Chaowu; Zhang, Zengrong; Qiu, Mohan; Wang, Yan
ABSTRACT : This study aimed to investigate the effects of different concentrations of in ovo injection of 25-hydroxycholecalciferol (25(OH)D3 ) on early growth, immune and tibia development in Daheng broilers. The results showed that 25(OH)D3 can significantly improve the hatchability of broilers and improve body weight ( p < 0.05). The low concentration of 25(OH)D3 (8 μg/mL) not only significantly increased tibial fresh weight, tibial length, tibial diameter, thymus and liver weight and immune organ index ( p < 0.05), but also significantly increased the content of bone metabolism-related factors OC and CaBP in serum and the expression levels of OC in the liver ( p < 0.05). However, a high concentration of 25(OH)D3 group (16 μg/mL) significantly increased bursa of Fabricius weight and immune organ index ( p < 0.05), the content of immune factor IL-2, IFN-γ and TLR15 in serum and the expression level of IFN-γ and TLR15 in the spleen ( p < 0.05). Furthermore, the content of ash, calcium and phosphorus in the tibia was negatively correlated with the expression level of OC and positively correlated with the expression level of ALP ( p > 0.05). Our data suggested that 25(OH)D3 has positive effects on the early growth, immune, bone development of broiler during the early stage, which is a supplement to improve disease resistance and skeletal development of broilers. Highlights: 25(OH)D3 can improve the hatchability of broilers and body weight. 25(OH)D3 have a beneficial effect on the immune system and tibia development of broilers at different time point. High concentration of 25(OH)D3 has the better effect on increasing the content of calcium and phosphorus in tibia.